Evaluate the competency of the construction machinery corporation’s division 2 – implication and improvement - Nguyen, Huu Toan (Khoa Quốc tế, ĐHQGHN, 2020)
The research provides recommendations on ways in which COMA2 can directly engaged in the design and improvement process. First, COMA2 must improve its brand image in the market (e.g., with better construction quality and quicker response to repair recalls, etc.). Second, make partnership with suppliers to ensure the quality, lower the costs, and the on-time material delivery. Third, improve the quality of the human resources. Importantly, it provides a road‐map for COMA2 for improving customer experiences. For the implementation, the COMA2 must have clear objectives and balance actions among three areas: customers, internal workforce, and cost‐efficiency. I would like my proposals would provide valuable contribution to COMA2 to make its business better.